2014
DOI: 10.1302/0301-620x.96b1.31569
|View full text |Cite
|
Sign up to set email alerts
|

Thromboprophylaxis with dabigatran leads to an increased incidence of wound leakage and an increased length of stay after total joint replacement

Abstract: Since the introduction of the National Institute for Health and Care Excellence (NICE) guidelines on thromboprophylaxis and the use of extended thromboprophylaxis with new oral agents, there have been reports of complications arising as a result of their use. We have looked at the incidence of wound complications after the introduction of dabigatran for thromboprophylaxis in our unit. We investigated the rate of venous thromboembolism and wound leakage in 1728 patients undergoing primary joint replacement, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 24 publications
(23 reference statements)
0
36
0
5
Order By: Relevance
“…при этом частота ВТэо у пациентов, получавших тромбопрофилактику дабигатраном (110 мг через 4 ч после операции и далее 220 мг в течение 14 дней), была выше (1,3%), чем у пациентов, получавших комбини-рованную тромбопрофилактику нМг (5000 Ме вечером накануне операции и далее ежедневно до выписки) с последующим переходом на аспи-рин по 150 мг в течение 6 нед. (0,3%, р = 0,047) [21]. однако существенное влияние на данный факт мог оказывать более продолжительный срок профилактики в группе сравнения: 2 нед.…”
Section: таблица 1/unclassified
“…при этом частота ВТэо у пациентов, получавших тромбопрофилактику дабигатраном (110 мг через 4 ч после операции и далее 220 мг в течение 14 дней), была выше (1,3%), чем у пациентов, получавших комбини-рованную тромбопрофилактику нМг (5000 Ме вечером накануне операции и далее ежедневно до выписки) с последующим переходом на аспи-рин по 150 мг в течение 6 нед. (0,3%, р = 0,047) [21]. однако существенное влияние на данный факт мог оказывать более продолжительный срок профилактики в группе сравнения: 2 нед.…”
Section: таблица 1/unclassified
“…Given the emerging trends of abbreviated inpatient stay following TJA and the increasing percentage of total joint arthroplasty performed in the outpatient setting, the search for reliable chemical anticoagulation agents that reduce VTE events while minimizing post-operative bleeding and wound complications is of great interest [37]. Not all new agents have been able to achieve these objectives consistently; many have been associated with an increased incidence of wound leakage and increased length of stay after total joint replacement [26]. Continued exploration of novel agents as they become commercially available is essential.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a significant increase in duration of hospital stay. Bloch et al demonstrated that the multimodal VTE prophylactic regimen of enoxaparin inpatient and extended use of aspirin after discharge resulted in significantly lower rates of symptomatic VTE, wound leakage and length of stay in post-operative total knee and total hip arthroplasty patients and resulted in the discontinuation of dabigatran for thromboprophylaxis [26].…”
Section: Aspirin Compared To Direct Thrombin Inhibitors (Dabigatran Amentioning
confidence: 99%
“…Factor IIa and Xa inhibitors administered orally may be associated with increased serous wound discharge and prolonged hospitalization . It is also not possible to fully reverse their anticoagulant effect . Long‐term use of aspirin is associated with gastrointestinal bleeding .…”
Section: Introductionmentioning
confidence: 99%
“…13 It is also not possible to fully reverse their anticoagulant effect. 14,15 Long-term use of aspirin is associated with gastrointestinal bleeding. 16 The NHMRC have recommended further research into the use of staged (sequential) chemoprophylaxis.…”
Section: Introductionmentioning
confidence: 99%